Pengaruh Organizational Learning Dan It Capability Terhadap Financial Performance - Sadat Amrul S; Enny Hardi (Jurnal Akuntansi dan Auditing Indonesia, 2010)
The purpose of this research is to study empirically the effect of organizational learning on financial performance through information technology capability as intervening variable. This research uses path analysis as an extension of multiple regression analysis. Population of this research is the go public manufacturing firms listing in Indonesian Capital Market Directory 2005 with top managers as the research sample. With 35,3 % respond rate, the statistical analysis result for the first hypothesis show that organizational learning has effect directly, negative and significant to financial performance. It means there is a competency traps. The statistical analysis result for the second hypothesis show that organizational learning has effect directly, positive and significant to information technology capability. It means there is a continuous learning process. The statistical analysis result for the third hypothesis show that information technology capability hasn’t effect directly to financial performance (p= 0,424). The statistical analysis result for the fourth hypothesis show that information technology capability is not significant as intervening variable.Keywords: organization learning, information technology capability, financial performance